2013
DOI: 10.1016/j.athoracsur.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Differential Tensile Strength and Collagen Composition in Ascending Aortic Aneurysms by Aortic Valve Phenotype

Abstract: Background Ascending thoracic aortic aneurysm (ATAA) predisposes patients to aortic dissection and has been associated with diminished tensile strength and disruption of collagen. ATAA arising in patients with bicuspid aortic valve (BAV) develop earlier than those with tricuspid aortic valves (TAV) and have a different risk of dissection. The purpose of this study was to compare aortic wall tensile strength between BAV and TAV ATAAs and determine if the collagen content of the ATAA wall is associated with tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 24 publications
10
99
2
Order By: Relevance
“…Pichamuthu et al [43], whereas disagree with the results of Vorp et al [31], which found non-significant difference between the two orientations.…”
Section: Influence Of Region and Orientationmentioning
confidence: 85%
See 1 more Smart Citation
“…Pichamuthu et al [43], whereas disagree with the results of Vorp et al [31], which found non-significant difference between the two orientations.…”
Section: Influence Of Region and Orientationmentioning
confidence: 85%
“…In particular, some studies move from the presentation of new tools in imaging analysis to evidence possible alterations in the morphology and in the micro-structure of the diseased aortic tissues [26,27]. Other studies focus on the use of mechanical tests (uniaxial and biaxial tensile tests) to evaluate and compare mechanical properties of both healthy and diseased tissues [28][29][30][31][32][33] and, at the same time, to investigate factors which can influence tissue properties like location and orientation [23,[34][35][36][37], patient age [30,38,39], patient sex [39,40], and presence of concomitant pathologies [25,33,36,[41][42][43][44].…”
Section: Introductionmentioning
confidence: 98%
“…The process is dynamic, highly heterogeneous, and may fluctuate as a function of local stress and biologic activity. Changes in the tissue microstructure caused by aging [23], disease progression [13], and underlying pathologies [27,28,29,30] significantly affect tissue structural organization and strength. One of the challenges of aneurysm simulation is the integration of dynamic wall weakening in the biomechanical model so that current estimates of local properties and local strength can be used to predict the risk of rupture.…”
Section: Assessment Of Aortic Wall Strengthmentioning
confidence: 99%
“…Tissue from the ascending aorta has been tested in a variety of configurations (reviewed by Avanzini et al [17]), with uniaxial and equibiaxial stretch tensile tests being the most common. In-plane uniaxial [18][19][20] and biaxial tension tests [21][22][23][24] provide information on tensile failure in the plane of the medial lamella ðr hh ; r zz Þ; and the biaxial tests can provide some additional information on in-plane shear ðr hz Þ. Although the dominant stresses in these tests may be the primary stresses during vessel rupture, they are not those driving dissection.…”
Section: Introductionmentioning
confidence: 99%